Temporal Variation and Respons of Mangrove Soil on Solar Illumination Changes - Christophil Medellu; . Soemarno; . Marsoedi; Sigfried Berhimpon (UNIVERSITY OF LAMPUNG, 2012)
Research on soil temperature in mangrove forest is a part of the mangrove ecosystem microclimate research. Studieson microclimate variables interaction, including soil temperature is important and interesting because it is associatedwith ecosystem and environmental changes, and the biota living in it. This study developed a mathematical modelingof soil temperatures and solar illumination in mangrove forest and the surrounding environment. Mathematicalmodeling function was constructed using data measured on three transects which different in ecosystem condition.The results showed that the mathematical modeling parameters produced the parameters of solar illumination andsoil temperatures that were difference for the three transects. Time lag of soil temperature on solar illumination wasalso diference in the three transects due to the difference of penetration of sun radiation and soil inundation by seawater. These parameters also showed the differences between the soil temperature in mangrove with the soiltemperature in terrestrial forest as studied by the former researcher. Our research demonstrated the charachteristicof soil temperature in mangrove, that was not merely controlled by sun radiation, but also it was contribute by thesea water and other factors.[How to Cite: Medellu C, Soemarno, Marsoedi and S Berhimpon. 2012. Temporal Variation and Respons of Mangrove Soil on Solar Illumination Changes. J Trop Soils 17 (2) : 67-74. Doi: 10.5400/jts.2012.17.2.165][Permalink/DOI: www.dx.doi.org/10.540/jts.2012.17.2.165]